Pemberdayaan Masyarakat Melalui Evaluasi Pelatihan UMKM Berbasis Digital - Joeliaty Joeliaty; Sri Djatnika Sya’diah Arrifin; Vita Sarasi; Yayan Firmansyah (Sekolah Tinggi Ekonomi Bisnis Syariah Bina Mandiri, 2023)
Community service is a form of mandatory activity carried out by every lecturer in carrying out the tridharma of higher education, with the aim of implementing theory and helping and providing input to the community in solving problems faced by the community. This year's Community Service was carried out virtually or online due to the covid-19 pandemic which required lecturers to carry out the community service programme (PPM) implementation process at home, still according to the rules given by the University. Since the COVID-19 pandemic, technology has played a major role in various activities, one of which is business for Micro, Small and Medium Enterprises (MSMEs). Through the use of social media and e-commerce, online marketing can reach a wider range of consumers. So that if MSME actors can maximize the use of social media and e-commerce, their income will increase and their products will be known throughout the region. Therefore, it is necessary to have digital-based training aimed at helping business actors to gain knowledge and have skills in using digital platforms. Through this PPM, we evaluate digital-based training that has been attended by MSME partners. Through this PPM, we evaluate digital-based training that has been attended by MSME partners. This programme service to the community is carried out virtually from July 10, 2021 – August 11, 2021. Technically, the implementation of this program is carried out from the stage of finding MSME partners, distributing questionnaires, to processing questionnaire data to evaluate the impact of digital-based training followed by MSME partners.